Poly[hexaaquatri-μ-malonato-didysprosium(III)] - Fang, Zhan-Qiang (International Union of Crystallography, 2008)
The title compound, [Dy(2)(C(3)H(2)O(4))(3)(H(2)O)(6)](n), forms a coordination polymeric structure comprising hydrated dysprosium ions and malonate ligands. In the asymmetric unit, there are one dysprosium ion, one and a half malonate ligands, and three water molecules. Each Dy(III) atom is coordinated by six O atoms from four malonate ligands and by three water molecules, and displays a tricapped trigonal–prismatic coordination geometry. The malonate ligands adopt two types of coordination mode, linking dysprosium centres to form a three-dimensional coordination polymer. The extensive network of hydrogen bonds in this polymer enhances the structural stability.